2007
DOI: 10.3390/12122579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-Aryl-3-phenethylamino-1-propanone Hydrochlorides as Possible Potent Cytotoxic Agents

Abstract: 1-Aryl-3-phenethylamino-1-propanone hydrochlorides 1-10, which are potential potent cytotoxic agents, were synthesized via Mannich reactions using paraformaldehyde, phenethylamine hydrochloride as the amine component and acetophenone, 4'-methyl-, 4'-methoxy-, 4'-chloro-, 4'-fluoro-, 4'-bromo-, 2',4'-dichloro-, 4'-nitro-, 4'-hydroxyacetophenone or 2-acetylthiophene as the ketone component. Yields were in the 87-98 % range. Of the compounds synthesized, compounds 2, 6-8 and 10 were new. The optimum reaction cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The chemial structures of the compounds were confirmed by 1 H-NMR, 13 C-NMR, UV, IR, and MS spectra and the purity level of the compounds was determined by elemental analyses. The spectral data of the mono-Mannich bases were reported in our previous study [50] and the spectral data for the piperidinol compounds are shown in Tables 1 and 2. The results of the elemental analyses for the piperidinols, which are reported here for the first time, are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemial structures of the compounds were confirmed by 1 H-NMR, 13 C-NMR, UV, IR, and MS spectra and the purity level of the compounds was determined by elemental analyses. The spectral data of the mono-Mannich bases were reported in our previous study [50] and the spectral data for the piperidinol compounds are shown in Tables 1 and 2. The results of the elemental analyses for the piperidinols, which are reported here for the first time, are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal reaction conditions for the synthesis of these compounds, 1-aryl-3-phenethylamino-1-propanone hydrochlorides, were investigated by changing the molar ratios of reactants and solvent, and the acidity level of the reaction medium using compound 1a and 9a as representative compounds from our previous paper [50]. It has been reported that the most suitable mol ratio of the reactants was 1:1.2:1, compared with 2:2:1 suitable for ketone, paraformaldehyde, and phenethylamine hydrochloride.…”
Section: Synthesis Of the Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as a precursor for the synthesis of p-hydroxyacetanilide and paracetamol (analgesic drug) [7]. It is also used as a ketone component in the manufacturing of 1-aryl-3-phenethylamino-1-propanone hydrochloride that is a potent cytotoxic agent [8]. Moreover, they are also used in manufacturing of cosmetics, flavours, and fragrances [9].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, coordination compounds with transition metals have been investigated in the last few decades after the discovery of cisplatin because they have shown good antineoplastic activity and less toxicity. [15,16] Literature survey shows that a large number of transition metal complexes of amides have been found to be associated with diverse pharmacological activities. [17] Complexes of transition metals with amides in proteins and peptides are utilized in numerous biological processes, such as oxygen conveyer, electron transfer and oxidation.…”
mentioning
confidence: 99%